Retraction Note: M2 macrophage-derived extracellular vesicles promote gastric cancer progression via a microRNA-130b-3p/MLL3/GRHL2 signaling cascade - Yu Zhang; Wenbo Meng; Ping Yue; Xun Li (Journal of Experimental & Clinical Cancer Research, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13046-020-01626-7.